Risk state Japan's foreign policy in an age of uncertainty - Maslow, Sebastian; Mason, Ra; O'Shea, Paul (Rethinking Asia and international relations., 2015)
Reformulating risk in its application to the study of international relations and foreign policy, this volume promises new insights into the analysis of contemporary foreign policy in East Asia and Japan's post-Cold War international relations in particular.